2022
DOI: 10.1186/s12302-022-00646-8
|View full text |Cite
|
Sign up to set email alerts
|

DRASTIC, GOD, and SI approaches for assessing groundwater vulnerability to pollution: a review

Abstract: Over the last three to four decades, several methods for assessing groundwater vulnerability to anthropogenic pollution have been developed. Researchers and policymakers have widely used these methods for preventing groundwater pollution through knowledge about particularly vulnerable areas. This systematic review presents different and significant methods for assessing the vulnerability of aquifers for the protection of the resource. Previous studies mentioned that formulating a single technique for assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 64 publications
(92 reference statements)
0
13
0
2
Order By: Relevance
“…For the GOD method, the O and D parameters have a major contribution to the vulnerability classes determination. Several studies agree that despite the possible differences found in the vulnerability results with the DRASTIC and GOD approaches, both methods have proven to be valid for acknowledging the general situation of groundwater quickly at low cost, easy data processing, and interpretation for decision-makers [7,22,40].…”
Section: Vulnerability Assessment: Drastic and God Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…For the GOD method, the O and D parameters have a major contribution to the vulnerability classes determination. Several studies agree that despite the possible differences found in the vulnerability results with the DRASTIC and GOD approaches, both methods have proven to be valid for acknowledging the general situation of groundwater quickly at low cost, easy data processing, and interpretation for decision-makers [7,22,40].…”
Section: Vulnerability Assessment: Drastic and God Methodsmentioning
confidence: 96%
“…This method considers five vulnerability classes: negligible (I V < 0.1), low (0.1 < I V < 0.3), medium (0.3 < I V < 0.5), high (0.5 < I V < 0.7), and extreme (0.7 < I V < 1). This method is primarily used in data-limited regions that require a succinct evaluation of the groundwater status [14,40].…”
Section: God Methodsmentioning
confidence: 99%
“…Therefore, the index-based methods are suitable for regions with data scarcity, especially arid regions. These models have frequently used for assessing groundwater vulnerability including DRASTIC , GOD (Huang et al 2013, Fannakh & Farsang, 2022, PI (Goldscheider et al, 2000), SINTACS (Al Kuisi et al 2006, Kumar et al 2013, etc. Moreover, overlay index-based approaches encompass rather subjective criteria for rating and weight assignment in context of vulnerability mapping.…”
Section: Previous Work Have Applied Different Techniques To Evaluate ...mentioning
confidence: 99%
“…Nevertheless, to produce a reasonably accurate result, the DRASTIC approach must be adapted to meet the specific hydrogeological demands of the region in which it is used [ 24 ]. To examine and evaluate the vulnerability of groundwater in the Ghiss Nekkor alluvial aquifer to pollution risk, many methodologies have been developed [ 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. However, there is no standard methodology for evaluating and validating an aquifer approach.…”
Section: Introductionmentioning
confidence: 99%